The relationship between fetuin-A level and the clinical features of patients with coronary artery disease associated with iron deficiency - M. O. Konovalova; N. S. Mykhailovska (Patologìâ)
The aim of the study: to assess the relationship between the level of fetuin-A and features of clinical hemogram, ferrokinetic parameters, vegetative and structural-functional changes of the myocardium in patients with coronary artery disease (CAD) associated with different stages of iron deficiency (ID).